High Prevalence Of Anti-Hepatitis A Virus Immunoglobulin G Antibody Among Healthcare Facility Attendees In Osogbo, Nigeria (2013)
The objectives of this study were to determine the prevalence of anti-hepatitis A virus (HAV) immunoglobulin G (IgG) antibody and associated factors among residents of Osogbo, a town in Nigeria with inadequate environmental sanitation and a shortage of potable water. This is a health facility–based study. Ninety one consenting, asymptomatic attendees of public healthcare facilities in Osogbo, Osun State, Nigeria, were consecutively selected for this study. Plasma samples of the study participants were tested for the presence of anti-HAV IgG using a HAV Ab Competitive Enzyme Immunoassay test kit. Ninety (98.9%) of the participants were seropositive for anti-HAVIgG antibody; group-specific prevalence was also high, but association of participants’ variables with the prevalence could not be obtained due to limited sample size and high group-specific prevalence. Since the hepatitis A vaccine is not currently used in Nigeria, the chance is high that the HAV IgG antibody–positive individuals were naturally infected; consequently Osogbo can be described as highly endemic for HAV infection.